Quantum algorithms for quantum dynamics - Miessen, Alexander; Ollitrault, Pauline J.; Tacchino, Francesco; Tavernelli, Ivano (Nature Computational Science, 2023)
Among the many computational challenges faced across different disciplines, quantum-mechanical systems pose some of the hardest ones and offer a natural playground for the growing field of quantum technologies. In this Perspective, we discuss quantum algorithmic solutions for quantum dynamics, reporting on the latest developments and offering a viewpoint on their potential and current limitations. We present some of the most promising areas of application and identify possible research directions for the coming years.